Use of tyrosine kinase inhibitors in the treatment of chronic myeloid leukemia (CML) - Almeida, C. B.; Souza, E. F.; Oliveira, G. G. (Scientific Electronic Archives, 2016)
Chronic Myeloid Leukemia is a hematological cancer that comes from translocation between chromosomes 9:22 t(9:22) (q34; 11), from which originates the BCR-ABL hybrid gene that is responsible for the alteration of protein kinase in leukemic cells. This atypical chromosome is called the Philadelphia chromosome and is present in most cases of CML. The triggering factor of this mutation is still unknown, however studies have reported a relationship with prolonged exposure to radiation. This disease has three characteristic phases: chronic phase, acute phase and blast crisis. It affects mostly men aged 55-60 years old, hardly emerging in children and youth. This disease accounts for approximately 15% of all existing leukemias. Because of its complexity, long treatment was not specific and patients progressed to death in a short time. However, with advances in research a breakthrough in the treatment of CML emerged with the development of tyrosine kinase inhibitors. The prototype of the first generation was imatinib mesylate, which offers to the patients more effective and lasting responses. However, some patients develop resistance during treatment and thus were developed dasatinib and nilotinib, which represent second generation of tyrosine kinase inhibitors, appearing more potent and less likelihood of resistance development. Tyrosine kinase inhibitors are more effective, efficient and powerful when compared to the previous treatment offered to patients with CML, besides having fewer side effects and fewer adverse reactions. This study aimed to carry out a review of the treatments used in CML with emphasis on the tyrosine kinase inhibitors from latest data. With the synthesis of new medicines options for the treatment of CML widened, it was permitted a greater therapeutic individualization. Notwithstanding the medications only control the disease and only curatively is bone marrow transplantation (BMT).